Cyclic Dipeptides Formation From Linear Dipeptides Under Potentially Prebiotic Earth Conditions - Guo, Yeting; Ying, Jianxi; Sun, Dongru; Zhang, Yumeng; Zheng, Minyang; Ding, Ruiwen; Liu, Yan; Zhao, Yufen (Frontiers in Chemistry, 2021)
Cyclic dipeptides (DKPs) are peptide precursors and chiral catalysts in the prebiotic process. This study reports proline-containing DKPs that were spontaneously obtained from linear dipeptides under an aqueous solution. Significantly, the yields of DKPs were affected by the sequence of linear dipeptides and whether the reaction contains trimetaphosphate. These findings provide the possibility that DKPs might play a key role in the origin of life.